Tax Elasticity and Buoyancy in Nepal: A Revisit - Timsina, Neelam (NRB Economic Review, 2007)
Tax elasticity and buoyancy estimates are the dynamic tools for measuring the tax performance. This study makes a revisit to the studies carried out earlier to measure tax elasticity and buoyancy in Nepal, in the context of the structural changes that have taken place in the tax system in recent years. The main objectives of the study are to measure the elasticity and buoyancy of tax and to ensure whether or not the tax system in Nepal is elastic. The study has applied time series regression approach for this empirical measurement. This study reveals that the tax system in Nepal is inelastic (less than unity) in the period 1975-2005 with a more than unitary buoyancy coefficients, thus reflecting that the bulk of revenue collection emanates from discretionary changes in the tax policy, rather than from automatic responses.